Decreased synaptic vesicle glycoprotein 2A binding in a rodent model of familial Alzheimer's disease detected by [18F]SDM-16 - Zheng, Chao; Toyonaga, Takuya; Chen, Baosheng; Nicholson, LaShae; Mennie, William; Liu, Michael; Spurrier, Joshua; Deluca, Kristin; Strittmatter, Stephen M.; Carson, Richard E.; Huang, Yiyun; Cai, Zhengxin (Frontiers in Neurology, 2023)
Synapse loss is one of the hallmarks of Alzheimer’s disease (AD) and is associated with cognitive decline. In this study, we tested [18F]SDM-16 (Zheng et al, 2021; Zheng et al, 2022), a novel metabolically stable SV2A PET imaging probe, in the transgenic APPswe/PS1dE9 (APP/PS1) mouse model of AD and age-matched wild-type (WT) control mice at 12 months of age. Based on previous preclinical PET imaging studies using [11C]UCB-J and [18F]SynVesT-1 in the same strain animals, we used the simplified reference tissue model (SRTM), with the brain stem as the pseudo reference region to calculate distribution volume ratio (DVR) values. To simplify and streamline the quantitative analysis, we compared the standardized uptake value ratio (SUVR) from different imaging windows to DVR values and found that the averaged SUVR values from 60-90 min post-injection (p.i.) are most consistent with the DVR values. Thus, we used averaged SUVR from 60-90 min for group comparisons and found statistically significant differences in the tracer uptake in different brain regions, e.g., striatum (p = 0.002), hippocampus (p = 0.001), thalamus (p = 0.003), and cingulate cortex (p = 0.0003). In conclusion, [18F]SDM-16 can be used to detect decreased SV2A levels in the brain of APP/PS1 mouse at one year old. Our data suggests that [18F]SDM-16 has similar statistical power in detecting the synapse loss in APP/PS1 mice as [11C]UCB-J and [18F]SynVesT-1, albeit later imaging window (60-90 min p.i.) is needed when SUVR is used as a surrogate for DVR for [18F]SDM-16 due to its relatively slower brain kinetics.